Mechanistic insights into 4-nitrophenol degradation and benzyl alcohol oxidation pathways over MgO/g-C3N4 model catalyst systems - P V R K Ramacharyulu; Abbas, Sk Jahir; Sahoo, Smruti R; Shyue-Chu Ke (Catalysis science & technology, 2018)
A series of g-C3N4-based visible light active photocatalysts was prepared by using melamine as a precursor and MgO as a dopant. The composites exhibited excellent photocatalytic activity in the degradation of 4-nitrophenol and selective oxidation of benzyl alcohol in aqueous media under a low-power visible LED light source. The composites oxidized benzyl alcohols to benzaldehydes with better selectivity and conversion efficiency in mild acidic conditions (pH 5–6) than in neutral conditions. When compared to pure g-C3N4, the as-synthesized MgO/g-C3N4 composites showed about five-fold enhancement in photocatalytic activity. EPR spectroscopy results revealed identical EPR signals from both g-C3N4 and MgO/g-C3N4 composites, thus confirming the presence of unpaired electrons with C2p character. Introduction of MgO into g-C3N4 resulted in an increased number of electrons trapped in the C2p states of g-C3N4, which manifested as an enhancement in the EPR signal intensity. The difference in the light and dark EPR spectral signal intensities verified the efficient charge separation in the as-synthesized MgO/g-C3N4 catalysts. Moreover, the double integral values of the visible and dark EPR spectral signal difference intensities matched well with the 4-nitrophenol degradation rate constants. This further confirms the importance of trapped electrons in C2p states responsible for the observed higher photocatalytic activities. Radical scavenging experiments evidenced electrons as the dominant active species responsible for 4-nitrophenol degradation, whereas both electrons and holes were observed to participate in the selective oxidation of benzyl alcohol. Furthermore, the scavenging experiments ruled out the possibility of either hydroxyl or singlet oxygen radicals influencing the rate of oxidation. This study demonstrates MgO/g-C3N4 as a viable photoactive material for applications related to environmental pollution abatement. The photoactive nature of the catalysts in aqueous media under a low-power visible LED light source further signifies their economic and ecological aspects, which can be exploited for other applications as well.